2012
DOI: 10.1186/1472-6920-12-39
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of questioning technique during classes in medical education

Abstract: BackgroundQuestioning is one of the essential techniques used by lecturers to make lectures more interactive and effective. This study surveyed the perception of questioning techniques by medical school faculty members and analyzed how the questioning technique is used in actual classes.MethodsData on the perceptions of the questioning skills used during lectures was collected using a self‒questionnaire for faculty members (N = 33) during the second semester of 2008. The questionnaire consisted of 18 items cov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 13 publications
(20 reference statements)
0
8
0
1
Order By: Relevance
“… 17 Some studies have clearly shown that what we think we are doing is far from what is really happening, due to a wrong perception of reality. 18 , 19 Awareness of a perception– reality gap in medical care is important when providing continuing medical education and may significantly alter behavior in beneficial ways for patient care. 20 The perceived period of preoperative fasting among patients undergoing surgery is hardly known.…”
Section: Discussionmentioning
confidence: 99%
“… 17 Some studies have clearly shown that what we think we are doing is far from what is really happening, due to a wrong perception of reality. 18 , 19 Awareness of a perception– reality gap in medical care is important when providing continuing medical education and may significantly alter behavior in beneficial ways for patient care. 20 The perceived period of preoperative fasting among patients undergoing surgery is hardly known.…”
Section: Discussionmentioning
confidence: 99%
“…If, for example, a question is posed and an instructor calls on the first person who raises their hand to answer, many students in the class will not have had time to generate a response, functionally rendering the questioning more of a "study" event than a "test" event. Thus, one simple but powerful suggestion for implementing whole-class questioning as opportunities to generate a testing effect include waiting a sufficient amount of time for a response (at least 3 to 5 seconds 29,30 ) to increase the chance that other students will have time to practice retrieval. Of course, even with extended wait time, not all students will engage in retrieval when a question is posed to a large class.…”
Section: Implementing Tests As Learning Toolsmentioning
confidence: 99%
“…Even though the utility of questioning in enhancing learning has been well documented, the time allotted for questioning in teaching and learning sessions is often negligible. 9,15 In the present study, specific questions were deliberately incorporated into the instructional design of histology lecture classes and considerable time devoted to them during the sessions to enhance learner engagement. Another common pitfall is the over-utilization of questions that require only factual recall to answer them.…”
Section: Discussionmentioning
confidence: 99%